P241 'CURE-CAP': A Comprehensive Admission & Discharge Pneumonia Care Bundle. (14th November 2013) - Cunningham, P; Burke, J; McCulloch, L; Varia, R
Abstract : Introduction: The annual incidence of Community acquired pneumonia (CAP) is 5–11/1000. Between 22% and 42% require admission to hospital. Wide variation exists in the management of CAP despite guidelines issued by the British Thoracic Society (BTS). Care bundles have been shown to improve outcomes through standardisation of care in other diseases as well as in CAP. A BTS/NHS Improvement initiative is due to launch a pneumonia admission bundle. However, it does not address the issue of standards around comprehensive discharge care. Objectives: To design and implement a care bundle for the management of CAP, that incorporates admission and discharge standards and to assess improvements post-implementation. Methods: We formulated a CAP bundle including a triage tool, with the acronym 'CURE-CAP', focussing on seven key standards (Fig. 1 ). Data was collected retrospectively on consecutive patients admitted to our GP Assessment Unit with a primary diagnosis of CAP with a 3-month period of implementation in between. Compliance to standards before and after implementation of the bundle was then measured. Results: The pre-implementation cohort had 43 patients (17 (40%) male; median (range) age 74 (36 –101)) and post–implementation cohort had 30 (8 (27%) male; median (range) age 82 (36–93)). Chest x-ray was performed within 4 hrs in 30/43 (70%) in the pre-implementation cohort, increasing to 30/30 (100%) post-implementation. Time from admission to x-ray improved as well (median (range) 2:49 (0:30–18:27) to 1:00 (0:21–2:42). Urgent oxygen assessment was performed in 100% cases in both cohorts. Recording of the CURB-65 severity score improved from 35/43 (81%) to 28/30 (93%). Early antibiotic administration (within 4 hrs) increased from 12/43 (28%) to 20/30 (68%) with appropriate (severity based) antibiotics selection improving from 29/43 (67%) to 28/30 (93%). The bundle led to total compliance with all discharge standards including appropriate smoking cessation counselling (5/7 (71%) to 4/4 (100%)), patient information leaflet provision (0% to 100%) and appropriate follow-up arranged (16/43 (37%) to 30/30 (100%)). Conclusions: We have successfully designed a CAP admission and discharge care bundle and shown improvements across all measured standards post implementation. A further study is planned to measure effects on direct patient outcomes.